An apparatus for external osteosynthesis of fractures in the distal one-third of the humerus - Bodnya, Oleksandr; Slavov, Vyacheslav; Krivenko, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The purpose of the present work was to improve the extrafocal method of reposition and fixation in fractures of the distal one-third humerus (DOTH) with regard for anatomical-physiological features of the fracture region. An improved variant of the device design and transosseous osteosynthesis (TOO) technology on the base of rods was used for DOTH fractures in 10 patients. The design of the device makes it possible to eliminate a displacement of humeral fragments and ensures their stable fixation, preventing any dysfunction of the elbow and shoulder joints. TOO was indicated by fractures of A (7 cases) and B (3 cases) types according to AO/ASIF classification. The analysis of treatment outcomes showed that the suggested technology of osteosynthesis made it possible to achieve good results (88.5 ± 1.3 points) in the majority of patients with the minimum number of complications.